Diaphragmatic motion recorded by M-mode ultrasonography: limits of normality - Boussuges, Alain (ERJ Open Res, 2021)
Chest ultrasonography has proven to be useful in the diagnosis of diaphragm dysfunction. The aim of the present study was to determine the normal values of the motion of both hemidiaphragms recorded by M-mode ultrasonography. Healthy volunteers were studied while in a seated position. Diaphragmatic excursions and diaphragm profiles were measured during quiet breathing, voluntary sniffing and deep breathing. Diaphragmatic excursions were assessed by M-mode ultrasonography, using an approach perpendicular to the posterior part of the diaphragm. Anatomical M-mode was used for the recording of the complete excursion during deep breathing. The study included 270 men and 140 women. The diaphragmatic motions during quiet breathing and voluntary sniffing were successfully recorded in all of the participants. The use of anatomical M-mode was particularly suitable for measurement of the entire diaphragmatic excursion during deep breathing. The statistical analysis showed that the diaphragmatic excursions were larger in men compared to women, supporting the determination of normal values based on sex. The lower and upper limits of normal excursion were determined for men and women for both hemidiaphragms during the three manoeuvres that were investigated. The lower limits of normal diaphragmatic excursions during deep breathing should be used to detect diaphragmatic hypokinesia, i.e. 3.3 and 3.2 cm in women and 4.1 and 4.2 cm in men for the right and the left sides, respectively. The normal values of the diaphragmatic motion and the lower and upper limits of normal excursion can be used by clinicians to detect diaphragmatic dysfunction.